HERD BEHAVIOR IN USING MOBILE PAYMENT WITH UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT2) - Rohmad Fuad Armansyah (Jurnal Manajemen dan Kewirausahaan, 2021)
The development of information technology, followed by higher bank competition, has encouraged innovation in providing various alternatives for non-cash payments. Mobile payment services are increasingly popular with the increasing use of smartphones in the last five years in Indonesia, so that financial behavior has shifted its function towards digitalization. This study aims to discuss the financial herding behavior of using mobile payments using the Unified Theory of Acceptance and Use of Technology (UTAUT2) approach. The data used is respondent data as many as 355 Indonesian students who use the mobile payment application on a mobile device. The results obtained by the variable performance expectance and price value have a significant effect on the behavioral intention of users of mobile payment applications in Indonesia. Then behavioral intention was proven to significantly influence usage behavior and herd behavior as a form of financial behavior deviation which was proven to affect performance expectations.